FACTORS INFLUENCING THE INTENTION TO CONTINUE USING THE MEKARI KLIK PAJAK APPLICATION IN INDONESIA - Jenarsi, Debby; Nathaniel, Andrean; Pandu Prasetya, Andreas; Dwi Pratiwi, Berlian; Erliza Putri, Desy; Intan Pambayun, Kezia Amadea (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This research aims to measure determinants that influence the continuance intention of using Mekari Klik Pajak Application in Indonesia. The method employed is quantitative research through a questionnaire distributed to 164 respondents. The analysis was conducted using Partial Least Square-Structural Equation Modelling (PLS-SEM) to test the relationships between the variables of information quality, system quality, and service quality as Information System Success Model (ISSM), confirmation, satisfaction, perceived usefulness as Expectation Confirmation Model (ECM), and continuance intetnion. The results show that only system quality and confirmation have a significant influence on satisfaction. Information quality haven’t a significant influence on satisfaction and perceived usefulness. Service quality has a significant influence on perceived usefulness but not on satisfaction. Additionally, satisfaction and perceived usefulness also haven’t a significant influence on continuance intention. In conclusion, integrating ISSM and ECM provides a better understanding of the factors that influence users' repeat usage of the Mekari Klik Pajak application.